2014
DOI: 10.1186/1866-1955-6-29
|View full text |Cite
|
Sign up to set email alerts
|

Visual motion processing deficits in infants with the fragile X premutation

Abstract: BackgroundFragile X syndrome (FXS) results from a trinucleotide repeat expansion (full mutation >200 cytosine-guanine-guanine (CGG) repeats) in the FMR1 gene, leading to a reduction or absence of the gene’s protein product, fragile X mental retardation protein (FMRP), ultimately causing cognitive and behavioral impairments that are characteristic of the syndrome. In our previous work with infants and toddlers with FXS, we have been able to describe much about their cognitive and visual processing abilities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…It generates internal models for behaviors, and guides the neocortex to store the most efficient representations for movement and high level cognitive and emotional processing (Koziol et al , 2012). Subtle under-development of the cerebellum may underlie developmental problems, including autism, anxiety and deficits in attention and visual motion processing that have been documented in children with fragile X premutation (Farzin et al , 2006, Gallego et al , 2014, Cordeiro et al , 2015) as well as motor impairment in FXPC− (O’Keefe et al , 2015). In FXTAS cerebellar structural damage becomes clinically observable, with MRI signal hyperintensities in the MCP being used as a diagnostic criterion (Brunberg et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It generates internal models for behaviors, and guides the neocortex to store the most efficient representations for movement and high level cognitive and emotional processing (Koziol et al , 2012). Subtle under-development of the cerebellum may underlie developmental problems, including autism, anxiety and deficits in attention and visual motion processing that have been documented in children with fragile X premutation (Farzin et al , 2006, Gallego et al , 2014, Cordeiro et al , 2015) as well as motor impairment in FXPC− (O’Keefe et al , 2015). In FXTAS cerebellar structural damage becomes clinically observable, with MRI signal hyperintensities in the MCP being used as a diagnostic criterion (Brunberg et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although sertraline did not produce significant language gains over placebo, it is interesting and encouraging for the families that the visual perceptual and fine motor skills of children with FXS were significantly improved by sertraline because these are common deficits seen in FXS. Visual perceptual problems, specifically reduced contrast sensitivity to second order movement, can be detected in the first year of life in eye-tracking studies of babies with FXS 13,14 . Subsequent visual perceptual problems including visual memory, visual spatial perception, and visual motor coordination are problematic in both males and females with FXS 5457 .…”
Section: Discussionmentioning
confidence: 99%
“…FXS is characterized by significant behavioral, cognitive, and emotional dysregulation including symptoms of anxiety, ASD, attention deficit hyperactivity disorder (ADHD), self-injurious behavior, irritability, aggression, impulsiveness, sensory processing vulnerabilities, and language deficits 511 . In addition, there are motor coordination deficits 11,12 and visual perceptual deficits; the latter of which have been documented even in infancy with eye tracking studies 13,14 . FXS is also highly associated with ASD; approximately 60% of patients with FXS also have ASD 7,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…This study examined 14 infants with the premutation and found visual processing deficits similar to infants with FXS, although their overall developmental scores were higher than those with FXS [36]. The findings suggested that deficits in spatiotemporal processing and subsequent executive dysfunction in some adults with the premutation may be present very early in life and emphasize the importance of studies examining early development of individuals along the spectrum of FMR1 mutations.…”
Section: Introductionmentioning
confidence: 99%